Perubahan Konsumen Digital: Mengantisipasi Perubahan Perilaku Konsumen dalam Bisnis E-Commerce Tahun 2024 - Agus Saputra (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This research aims to analyze the changes in digital consumer behavior in the context of e-commerce business until 2024. Through a qualitative approach with a focus on literature studies, the analysis identifies factors that influence changes in digital consumer behavior, including increased online shopping activities, shifting purchasing preferences, the use of mobile devices, digital payment trends, data security and privacy, and the influence of social, cultural, and new technological factors. The analysis shows that consumers are increasingly demanding better user experience, flexibility in payment methods, and guaranteed data security and privacy. Meanwhile, new technologies such as artificial intelligence and collaboration with influencers also play an important role in influencing consumer behavior. Thus, the proposed suggestions include improving user experience, flexibility in payment methods, investment in new technologies, collaboration with influencers, and prioritizing data security and privacy. It is hoped that the results of this study can help e-commerce businesses to better understand the changes in digital consumer behavior and develop effective strategies in dealing with them.